2008
DOI: 10.1371/journal.ppat.0040041
|View full text |Cite
|
Sign up to set email alerts
|

Nanobacteria Are Mineralo Fetuin Complexes

Abstract: “Nanobacteria” are nanometer-scale spherical and ovoid particles which have spurred one of the biggest controversies in modern microbiology. Their biological nature has been severely challenged by both geologists and microbiologists, with opinions ranging from considering them crystal structures to new life forms. Although the nature of these autonomously replicating particles is still under debate, their role in several calcification-related diseases has been reported. In order to gain better insights on this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
122
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(134 citation statements)
references
References 31 publications
11
122
1
Order By: Relevance
“…The existence of nanobacteria has been openly questioned by a number of scientists (17)(18)(19). In effect, some scientists argue that nanobacteria are not living entities but are composed of salts and other physiologically based organic compounds.…”
mentioning
confidence: 99%
“…The existence of nanobacteria has been openly questioned by a number of scientists (17)(18)(19). In effect, some scientists argue that nanobacteria are not living entities but are composed of salts and other physiologically based organic compounds.…”
mentioning
confidence: 99%
“…Other investigators -Martel and Young, 9 Wu et al, 6 and Raoult et al 10 -did not obtain the same result when they used the same method. Anti-CNP monoclonal antibodies have high sensitivity and low specificity, which explains the failure to achieve cross-reactions with serum protein (albumin and fetuin-A) in other studies.…”
Section: 2mentioning
confidence: 84%
“…Calcifying NP antigens and antibodies were detected significantly more often in CNP-containing diseases compared to controls. 2 Although many studies [5][6][7][8]10 proposed that CNPs might have the ability to form mineral-protein complexes in normal serum in physiological conditions, in reality, Kajander et al reported that this could not be totally true. 37 However, mineral-protein complexes have been shown in a gammairradiated serum study model by Martel and Young.…”
Section: 2mentioning
confidence: 99%
See 2 more Smart Citations